A Vision for Public Health Transformation in Pakistan Beyond the Pandemic Era - SHUJA, ARSLAN (Pakistan Journal of Medical & Health Sciences, 2025)
The global health paradigm has been profoundly changed by the COVID-19 pandemic. It was also the crucible of crisis and a rare catalyst for systemic reflection for Pakistan. With a legacy of fragmented healthcare delivery, low health expenditures, and pervasive health inequities, a country was forced to face down all fronts, from the fragility of supply chains and of overworked hospitals, to digital divides and misinformation. However, out of this adversity, there was a generational opportunity to transform Pakistan’s public health infrastructure at its core. A future-proof health system will not just want to control disease, it will be based on equity, powered by data, driven by prevention, and shock-resilient.1, 2. Rethinking Public Health as A National Development Priority Public health must rise from the periphery to the center of national development following the pandemic. This begins with political will. Currently, Pakistan’s health expenditure (around 1.2% of GDP) is one of the lowest in the region. It needs increased, sustained investment as well as strategic spending. We also have to channel funds not just to tertiary care institutions but also to community-level infrastructure, maternal and child health services, non-communicable disease (NCD) prevention, and health literacy. As climate resilience, food security, education, and other public health needs are a part of the development agenda, not only.3. From Hospital-Centric to People-Centric Care Pakistan has always had a model of healthcare in favour of urban and hospital-based care. But the pandemic emphasised the importance of distributed, community-driven services. The backbone of health service delivery must be the revitalized Basic Health Units (BHUs), mobile clinics, and telemedicine that will strengthen the Primary Health Care (PHC) network. These services must integrate preventive care, early disease screening, immunization outreach, and nutrition support. However, programs like the Sehat Sahulat Card under the rubric of Universal Health Coverage (UHC) are a promise, and their coverage, efficiency, and equity need to be evaluated independently and continuously improved.4. Harnessing Data, Technology, and Innovation Digital health systems showed their potential to be used in real time during COVID-19 through dashboards, contact tracing apps, and genomic surveillance. These tools must now be institutionalized in Pakistan. An electronic medical records system would be created across provinces and health facilities to allow better disease surveillance, resource allocation, and continuity of care for patients. At the same time, investment in digital health literacy and protection of data privacy must be made. Further democratizing health access can be accomplished through the integration of AI-based diagnostics, drone-assisted delivery in remote areas, and low-cost point-of-care devices.5. Rebuilding the Health Workforce with Equity and Dignity The pandemic also exposed Pakistan’s structural vulnerabilities of its health workforce, especially frontline workers, nurses, and lady health workers, to disproportionate burdens of work with insufficient protection and compensation. Pakistan has a low health worker-to-population ratio compared to WHO benchmarks. A transformative vision will also need a national strategy for increasing the size of the workforce, fair remuneration, gender equity in employment, and continuous professional development. Partnerships with medical and public health universities should also foster a new generation of trained epidemiologists, biostatisticians, and health management graduates ready for the 21st century.6. Putting Public Health in the Heart of Multisectoral Governance The social determinants of health are public health; they include clean water, air quality, food security, housing, education, and gender rights. Therefore, inter-ministerial collaboration is non-negotiable. There must be alignment of health objectives in the policies of the ministries of planning, environment, education, and agriculture. Walkability and air pollution should be part of urban planning; climate change mitigation has to take into account vector-borne diseases; health literacy should be part of school curricula. Only through systems-level integration can Pakistan have health in all policies7. Resilience, Trust, Accountability: The Road Ahead Resilient systems, transparent governance, and public trust will be the key to a truly transformed public health landscape in Pakistan. Transforming from a conventional corporation requires civil society, academia, and the private sector to be co-creators in the process. Reinvigoration of regulatory mechanisms for health service quality, ethical data use, pharmaceutical safety, and research oversight is needed. Misinformation must be countered and trust in science strengthened through public engagement campaigns, using media, religious leaders, and educational institutions.8. CONCLUSION Pakistan stands at a crossroads. Although tragic, the pandemic showed the fragility and potential of its health systems. This is the time for deliberate, visionary, and inclusive reform. It is not enough to say ‘business as usual’; that is simply unacceptable. The new public health framework ought to be reimagined with every Pakistani entitling to the right to health, prepared for the next pandemic, and progressing national well-being through resilience, equity, and innovation. The world is watching as the future waits.